2019
DOI: 10.1016/j.jad.2019.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the real-world effectiveness of a cognitive behavior therapy-based transdiagnostic program for emotional problems in children in a regular school setting

Abstract: Background: The present study examined the real-world effectiveness of a transdiagnostic prevention programme, Super Skills for Life (SSL), among children with emotional problems in regular school settings. SSL is based on the principles of Cognitive Behaviour Therapy (CBT), behavioural activation, and social skills training. Methods: Participants were 205 children, aged 8 to 12 years, who were referred by their teachers as having significant emotional problems. All the children completed measures of emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 51 publications
11
41
0
3
Order By: Relevance
“…The program comprises two resource materials: the facilitators' manual and a workbook for the children which contains all the activities and homework. The facilitator's manual contains structured steps on how to deliver SSL; a recent study by Essau et al (2019) indicated that SSL can be delivered effectively by SSL-trained professionals with a wide range of expertise and disciplines (e.g., social work, counselling, teaching). The methodology used for learning techniques/skills varied (e.g., reading and individual or group exercises, social performances thorough videotaped role-playing, video feedback with prior cognitive preparation, and homework) together with continuous reinforcement, ensuring that the children receive positive experiences during the sessions.…”
Section: Super Skills For Lifementioning
confidence: 99%
“…The program comprises two resource materials: the facilitators' manual and a workbook for the children which contains all the activities and homework. The facilitator's manual contains structured steps on how to deliver SSL; a recent study by Essau et al (2019) indicated that SSL can be delivered effectively by SSL-trained professionals with a wide range of expertise and disciplines (e.g., social work, counselling, teaching). The methodology used for learning techniques/skills varied (e.g., reading and individual or group exercises, social performances thorough videotaped role-playing, video feedback with prior cognitive preparation, and homework) together with continuous reinforcement, ensuring that the children receive positive experiences during the sessions.…”
Section: Super Skills For Lifementioning
confidence: 99%
“…Crossover effects from prevention programs that focus exclusively on either anxiety or depression further support the idea of targeting both symptom categories with the same intervention [18]. There are few studies of such interventions for youth, but the results to date are generally promising [19][20][21][22]. In addition, there are studies that focus on the prevention of both anxiety and depression without using the term "transdiagnostic"; one example is the Aussie Optimism; Positive Thinking Skills Program for the prevention of depression and anxiety in school-aged children.…”
mentioning
confidence: 99%
“…Several studies have shown the effectiveness of SSL in reducing anxiety and depressive symptoms, and in enhancing self-esteem among children (Essau et al, 2014(Essau et al, , 2019. No studies have been conducted using the adolescent version of SSL.…”
mentioning
confidence: 99%